DECIPHERING INCOME, PROFIT, AND THEIR DETERMINANTS OF ORGANIC AND CONVENTIONAL ROJOLELE RICE FARMING IN KLATEN REGENCY - Rahmawati, Dyah; Jamhari, Jamhari; Irham, Irham (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Rojolele rice is a superior commodity from Klaten Regency, known for its premium quality and distinctive flavor. Rojolele can be grown both organically and conventionally. Organic farming systems have many advantages, especially in terms of income and profitability; however, most farmers still practice conventional methods. The objectives of this study were: (1) to compare the income and profit of organic and conventional rojolele rice farming, and (2) to determine the factors that affect the income and profit of rojolele rice farming in Klaten Regency. This study used a survey method involving 20 organic farmers and 47 conventional farmers. The analytical method employed is an income and profit analysis, as well as multiple regression analysis. The results of the study showed that the income from organic rojolele rice farming is Rp 30,988,293 per hectare over two growing seasons, which is higher compared to conventional farming (Rp 20,463,484). Meanwhile, the profit for organic farmers is Rp 18,686,701 and for conventional farmers it is Rp 14,106,446. This indicates that organic rojolele rice farming is more profitable than conventional. Statistically, organic and conventional rojolele rice farming shows significant differences in income, though not in profit value. The factors significantly affecting income for organic farmers are land area, while in conventional farming, they are the price of chemical pesticides and land area. Furthermore, the factor influencing the profit of rojolele farmers, both organic and conventional, is solely the land area. Therefore, it may be considered to expand the development of organic rice farming, particularly rojolele rice, in Klaten Regency.